Newcastle disease virus induces degradation of folliculin to regulate host cell energy metabolism and facilitate viral replication - Mengqing Yang; Xianjin Kan; Xinna Li; Yingjie Sun; Ying Liao; Xusheng Qiu; Lei Tan; Cuiping Song; Chan Ding (Poultry Science)
Viral replication is an energy-intensive process that often induces energy stress in host cells, and efficient mobilization of host cell energy resources facilitates optimal viral replication. The mechanisms by which Newcastle disease virus (NDV) regulates the host energy metabolism to facilitate its replication remain incompletely understood. For this purpose, transcriptomic analysis was conducted to delineate the transcriptional changes during NDV infection. The results demonstrated that NDV infection downregulated the transcriptional levels of enzymes associated with de novo fatty acid synthesis. Subsequent investigations demonstrated that the active form of the sterol regulatory element-binding protein 1c (SREBP1c) a master transcription factor governing lipid biosynthesis pathways, exhibits reduced expression following viral infection. Notably, SREBP1c activation is negatively regulated by folliculin (FLCN), a tumor suppressor protein that undergoes during NDV infection. The de novo fatty acid synthesis pathway is an energy-intensive process, and the degradation of FLCN may suppress this pathway to maintain cellular energy homeostasis, thereby supporting viral replication. In summary, our findings demonstrate that NDV facilitates its replication by inducing degradation of FLCN, thereby modulating the host cell energy metabolism.